Agronomic performance and gaseous exchanges of the radish under saline stress and ascorbic acid application - Leal, Ygor Henrique; Vieira de Sousa, Leonardo; da Silva, Toshik Iarley; Gomes de Moura, Joana; Sousa Basílio, Ana Gabriela; Melo Filho, José Sebastião de; Gonçalves, Anderson Carlos de Melo; Dias, Thiago Jardelino (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The radish is a short-cycle vegetable that has excellent nutritional and medicinal properties. It is considered rustic, meaning it tolerates adverse conditions with the possibility of being irrigated with saline water, which creates stress. In this context, this study aimed to evaluate the effect of electrical conductivities in irrigation water and doses of ascorbic acid on the agronomic performance and gaseous exchanges of radishes. This experiment was carried out in a protected environment at the Agricultural Sciences Center of the Federal University of Paraíba, Areia, Paraíba (Brazil). The experiment design used randomized blocks with five doses of ascorbic acid (0.0, 0.29, 1.0, 1.71 and 2.0 mM) and five electrical conductivities in the irrigation water (0.5, 1.3, 3.25, 5.2 and 6.0 dS m-1), with four replicates. The growth, gas exchange and production were evaluated. The doses of ascorbic acid were not significant. The increase in the electrical conductivities of the irrigation water provided a reduction in the agronomic performance and gas exchanges, except for the net photosynthesis, water use efficiency and instantaneous carboxylation efficiency, which were not significant. There was a relationship between the net photosynthesis, transpiration, internal concentration of CO2 and water use efficiency and the stomatal conductance. The agronomic performance and gaseous exchanges of the radish culture were influenced by the salinity. The foliar application of ascorbic acid did not influence the agronomic yield and gaseous exchanges of the radishes at the tested doses.